The Chemical, Microbiological, and Sensory Characteristics of Cangkuk: a Fermented Beef Meat from Kuantan Singingi, Riau Province - Mirdhayati, Irdha (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
Traditional fermented meat products made from the flesh food in Indonesia are still rare, one of which is interesting to study is cangkuk. This research was conducted to study of the details cangkuk processing, the chemical, microbiological, and sensory characteristics of cangkuk originating Kuantan Singingi. The research consists of two stages (1) surveys and interviews regarding raw materials, formulations, processing methods and sociology of cangkuk, (2) analysis of their chemical, microbiological and sensory characteristics. Sampling method of the cangkuk by purposive sampling, derived from four villages : Sungai Manau, Kinali, Inuman and Pangean. Data analysis was done descriptively. The result showed that the processing of cangkuk had three formulations according to ratio between meat: bamboo shoots and or kepayang seeds:(2:1);(1:1);(1:1,7). Fermentation progress in anaerobic condition for seven days. The chemical characteristics were as follows: the content of water, protein, lipid, ash and pH value were 68-71%, 18-19%, 1,8-2,3%, 1,2-1,6%, 3,6-5,2, respectively. The total lactic acid bacteria (LAB) were 103-108 cfu/g, negative Salmonella, and total E.coli was <3-9,4 mpn/g. The sensory characteristic showed typical of color, sting aroma and meat texture was slightly tender. It can be concluded that the processing of cangkuk from Kuantan Singingi identified by ratio of raw materials and variety of fermentation media, good in chemical characteristic and total LAB, had typical sensory characteristic, but still contaminated E. Coli.